Penanganan Bagi Anak Berkebutuhan Khusus, (Tuna Grahita) - Graces Maranata; Dina Rotua Sitanggang; Stefani Hagelara Pakpahan; Emmi Silvia Herlina (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
Children with special needs are children born with special needs that are different from humans in general and require special services. A person with a barrier of intelligence has been assured that he is a person with a disability. Children with tunagrahita have a tendency to care less about the environment, either in the family or the surrounding environment. Society generally recognizes tunagrahita as mental retardation or mental retardation or idiot. According to Kustawan, D. (2016) is a child who has a significant intelligence below average and accompanied by an inability to adapt the behavior that emerged in the development period. He also said that children with tunagrahita have academic obstacles such that in the learning service requires modification of curriculum that suits their particular needs. In line with the opinion of Kustawan that children with tunagrahita have barriers in processing learning for children in general. Although child retardation has these barriers, it does not close the opportunity to receive proper and proper education both at home and especially at school. In order for a child with tunagrahita to have a bright future, just like a child in general.